PENGARUH MODEL PEMBELAJARAN THINK TALK WRITE TERHADAP KEMAMPUAN MENULIS TEKS EDITORIAL - Nella Darbiah Nasution; Diah Kusyani; Siti Fatimah Zahara (Jurnal Bahasa Indonesia Prima (JBIP), 2023)
This research was conducted to find out how the influence of the think talk write learning model on students' ability to write editorial texts properly and correctly. This research was located at the PAB 1 Helvetia Vocational School, Jl. Veterans Psr. IV Pulo Brayan Medan. The method in this research uses the one-group pretest-posttest experimental model and random sampling technique with a total population of 126 students. The data collection tool used was a written test in the form of an essay. The ability to write editorial texts using the think talk write learning model obtained perfect scores for 6 students with a percentage of 17.6%. The excellent category is 23 students, with a percentage of 67.6%. Enough category as many as 5 students with a percentage of 14.7%. However, for the fewer and significantly fewer categories, none were found. This means that the ability to write editorial texts is at a good level due to the influence of the think-talk write learning model. Thus the hypothesis is accepted, namely that there is an influence of the think talk write learning model on the ability to write editorial texts in XII students of SMK PAB 1 Helvetia in the 2022-2023 academic year.